Improving students' interest in IPS lessons by Inquiring Minds Want to Know learning model - Khadijah, Khadijah (Universitas Riau Kepulauan, 2023)
This study aims to determine the increase in student interest in social studies subjects through the Inquiring Minds Want to Know model. This research includes planning, implementation, observation, and reflection. The research took place in 2 cycles with a sample of 34 students of class IX G SMP Negeri 34 Batam. Data collection techniques using observation, interviews, documentation and questionnaires. The validity of the research data using data triangulation with quantitative analysis. The results of this study indicate that learning using the Inquiring Minds Want To Know method is able to increase student learning interest, this is supported by an increase in fun and competition during learning, this can be seen from the results of the pre-action questionnaire of 62.3% increasing to 68.03% in cycle I, and in cycle II it increased to 73.3% and was supported by observations from cycle I of 56.5% to cycle II of 73.8%, an increase of 17.3%. From the results of observations and questionnaires, it was obtained that the average student interest in the first cycle was 62.4% and 73.6% in the second cycle. This means that students' interest in learning has exceeded the success criteria of the action set, namely 70%.